THE FEDERAL SUPREME COURT AND THE INTERVENTION OF THE JUDICIAL POLICY IN PUBLIC POLICIES:AN ANALYSIS OF THE LEGAL (IN)FEASIBILITY OF THE GENERAL REPERCUSSION THESIS SET FORTH IN TOPIC 698 (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The present work deals with the thesis of general repercussion established in item 698, of the Federal Supreme Court, in relation to the intervention of the Judiciary in public policies aimed at the realization of fundamental rights. In this perspective, we seek to analyze the legal feasibility of using coercive judicial support measures during the compliance phase of decisions on the implementation of public policies. In the end, it is concluded that, in addition to the material restrictions, there is a purely legal limitation, consisting in preventing the use of specific coercive support measures that go beyond the mere generic determination to present an action plan by the defendant itself in the deal. Thus, in view of the recent thesis of general repercussion fixed in topic 698, so that the judicial decision on the implementation of public policies does not get lost in factual unenforceability, it will be up to the judge to act as a true negotiator, since his powers of coercion, legally, now are limited to the mere determination to present the plan to be prepared by the Public Administration itself.